Rotary enclosing control of second-order multi-agent systems for a group of targets - Shi, Y.; Li, R.; Teo, Kok Lay (2016)
© 2016 Taylor & Francis This paper investigates the rotary enclosing control of a second-order multi-agent system around a group of moving targets. The concepts of the central estimator and the rotary enclosing control for targets are introduced. Based on the target estimators, the enclosing control protocol is constructed and the convergency of the control protocol is established. With the proposed control protocol, the given enclosing structure can be achieved and the agents can keep on moving in rotatory formation according to given centripetal acceleration. Finally, simulation studies are carried out by using the proposed method so as to demonstrate its applicability.